2018
DOI: 10.3399/bjgp18x694997
|View full text |Cite
|
Sign up to set email alerts
|

The impact of new forms of large-scale general practice provider collaborations on England’s NHS: a systematic review

Abstract: Good-quality evidence of the impacts of scaling up general practice provider organisations in England is scarce. As more general practice collaborations emerge, evaluation of their impacts will be important to understand which work, in which settings, how, and why.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 20 publications
(29 reference statements)
2
29
0
Order By: Relevance
“…There is a growing interest in the topic of general practices working together, 61 with various researchers seeking to add to the knowledge on this topic. We designed this study to be different from, but also complementary to, other approaches that emphasise large-scale data collection via surveys 118 and/or that focus on federations, which may be more developed than is typical, nationally.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…There is a growing interest in the topic of general practices working together, 61 with various researchers seeking to add to the knowledge on this topic. We designed this study to be different from, but also complementary to, other approaches that emphasise large-scale data collection via surveys 118 and/or that focus on federations, which may be more developed than is typical, nationally.…”
Section: Methodsmentioning
confidence: 99%
“…A recent systematic review of new forms of large-scale general practice provider collaborations in England 61 (see Appendix for more detail) found that larger scale could contribute positively to sustainability in general practice through standardised processes and operational efficiency, maximising income, enhancing the workforce and deploying technology. However, it highlighted the significant levels of leadership and resources needed to create, develop and maintain these organisations.…”
Section: General Practice Collaborative Working: a Recent Historymentioning
confidence: 99%
See 3 more Smart Citations